2003
DOI: 10.1590/s0100-879x2003001000007
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of short stature and socioeconomic status on body mass index and weight gain during reproductive age in Brazilian women

Abstract: Short stature, a marker for undernutrition early in life, has been associated with obesity in Brazilian women, but not in men. We tested the hypothesis that weight gain during the reproductive years could explain this gender difference. A national two-stage household survey of mothers with one or more children under five years of age was conducted in Brazil in 1996. The subjects were women aged 20 to 45 years (N = 2297), with last delivery seven months or more prior to the interview. The regions of the country… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
5
15
1
3
Order By: Relevance
“…Within this context, height deficits observed inside the uterus and/or in the early childhood could determine the short height of adults. 9,24,25 In the present study, most mothers were short, which is also found in other studies with populations that were subjected to chronic hunger, determining the cycle of childhood malnutrition, short height, obesity, and comorbidities in adulthood. [26][27][28] At present, we also demonstrated that statistically, regardless of the nutritional status of mothers, shorter height was directly associated with child malnutrition.…”
Section: Maternal Characteristicssupporting
confidence: 87%
“…Within this context, height deficits observed inside the uterus and/or in the early childhood could determine the short height of adults. 9,24,25 In the present study, most mothers were short, which is also found in other studies with populations that were subjected to chronic hunger, determining the cycle of childhood malnutrition, short height, obesity, and comorbidities in adulthood. [26][27][28] At present, we also demonstrated that statistically, regardless of the nutritional status of mothers, shorter height was directly associated with child malnutrition.…”
Section: Maternal Characteristicssupporting
confidence: 87%
“…Segundo Ong 23 , o baixo peso ao nascer, associado à introdução tardia de alimentos complementares e a uma maior incidência de diarreia, favorecidos pela insalubridade do meio ambiente, pode determinar a alta prevalência de desnutrição observada em populações menos favorecidas, como as de nosso estudo. Dentro desse contexto, déficits estaturais observados intrauterinamente e/ou na primeira infância poderiam determinar a baixa estatura dos adultos 9,24,25 . 0 = informantes com condição menos favorável e/ou menor/igual em relação ao ponto de corte definido a priori ; 1 = informantes com condição mais favorável e/ou igual/ maior em relação ao ponto de corte também definido a priori ; IMC = índice de massa corporal; RC = razão de chances ajustada para "peso da criança ao nascer".…”
Section: Discussionunclassified
“…The major increase in BMI after pregnancy among low-stature women in urban areas, independent of parity, clearly demonstrates the risk of a higher gestational weight gain and its retention after delivery in the most developed areas in the country (42).…”
Section: Current Methods In Brazilmentioning
confidence: 99%
“…Because low stature is a marker of previous malnutrition, it is important to ensure adequate gestational weight for low-stature women (42). On the other hand, among these cases, excessive weight may be associated with cephalopelvica disproportion (11,27,28).…”
Section: Current Methods In Brazilmentioning
confidence: 99%